Exuding Moral Character or Rocking the Boat? Observers' Reactions Towards Displays of Workplace Moral Courage - Li, Yanhong (Université d'Ottawa / University of Ottawa, 2022)
Moral courage captures one's ability to do 'what is right' for 'the greater good' in situations where doing so involves personal danger, risks, or difficulties (Detert & Bruno, 2017; Rate, 2010). Recognizing the organizational and social benefits of moral courage, management researchers and practitioners alike encourage business students and employees to engage in morally courageous behaviours (Comer & Sekerka, 2018; Sekerka & Godwin, 2010). However, we lack the understanding of how others perceive and react to organizational members' acts of moral courage (Detert & Bruno, 2017). This dissertation examines how individuals react to displays of workplace moral courage. I argue that although by and large people do respond favourably towards employees who engage in workplace moral courage, the extent to which such responses are (un)favourable is dependent on characteristics of both the actor (i.e., gender) and the observer (i.e., social dominance orientation). I conduct three pilot studies and three hypotheses testing studies as part of my dissertation. The hypotheses testing studies include two experimental designs and one field-survey design and examine both peer- and supervisor responses to employees' acts of moral courage. While the effects of actor's gender and observers' social dominance orientation on observers' reactions towards workplace moral courage did not fully replicate across all three studies, the pattern of the findings was generally consistent.
Keywords: moral courage; moral character; social dominance; gender